Migration and Social Cohesion: Appraising the Resilience of Place in London. Issue 5 (July 2015) - Hickman, Mary J; Mai, Nicola; Phillips, Deborah; Robinson, David
Abstract This paper is based on research designed to understand how previous immigrations are perceived/experienced and how this informs the contemporary moment of immigration. We explored the actual lived lives and practices of both new immigrants and long‐term settled populations in six places across the UK. We were particularly interested in layered histories of migration, and historically constituted diaspora spaces, that is, the spaces of multiculture encounter in all their specificities and the relevance of this for social intervention policies in the UK. We emphasize the importance of understanding social cohesion and the nation through the formation and (re)formulation of prevailing narratives of belonging, obligation, and identity. These narratives inform the way that social heterogeneity, resulting from social and geographical mobility and the porousness of multiculture spaces of encounter, is managed in different places and at different levels, encompassing the global, the national, and the local dimensions. This paper considers material drawn from in‐depth life narrative interviews in the two sites that we researched in London: Kilburn in the north‐west of the city and Downham in the south‐east. The research aimed to engage with Downham and Kilburn in an exploration of the complexity of 'cosmopolitan' London by exploring the way in which the historical experience of migrancy and hybridity (or its lack) can be a factor sustaining (or hindering) social cohesion. Both places are socially and economically deprived areas, but they constitute examples of contrasting responses to contemporary immigration. Copyright © 2015 John Wiley & Sons, Ltd.